Market solutions to the low-income housing challenge – a case study of Bulawayo, Zimbabwe - Taruvinga, Bridgit Gugulethu (Department of Construction Economics and Management, 2020)
The provision of decent, affordable and well-located housing for low-income communities has been an intractable problem, especially for developing countries. The empirical puzzle that motivated this study is that, despite the adverse macro environment in Zimbabwe, there appears to be private-sector developers who are successfully developing housing benefiting the low-income group. This is so, despite numerous studies that claim that given the magnitude of the housing challenge, a neoliberal doxa in a developing country context as a solution is a fallacy. Working on the broad premise that these developments represent a successful adaptation to the structural environment, the main question guiding the study was - what accounts for the success of market provided low-income housing developments in Zimbabwe despite the environment not being conducive for it? The two sub-questions flowing from this main question were firstly, how does the structural environment enable and/or constrain private sector low-income developments in Zimbabwe? Secondly, what strategies do developers adopt in response to the structural enablers and/or constraints to develop low-income housing in Zimbabwe? From these questions, the study has two hypotheses – the first hypothesis is that despite the adverse environment there exists in Zimbabwe structural enablers that make market solutions to the low-income housing challenge possible. The second hypothesis states that developers have specific discernible strategies that they employ in response to the adverse operating environment to reduce development costs to levels that enable them to provide low-income housing successfully. Using the Structure-Agency model, which is a theoretical framework rooted in institutional economics, a conceptual model to study the development process was developed and used to theorise the impact of structure on agency in the development process. Empirical evidence was gathered using observation, household surveys, and semi-structured interviews. This evidence was obtained from five housing schemes, the local authority, central government, financiers and the developers of the housing schemes, and then processed using NVIVO and SPSS. The study finds that most challenges faced by developers emanate from the institutional environment and access to resources. These challenges are namely central-local government dynamics fuelled by political undertones, lack of access to land suitable for the target group, a bureaucratic and stiff regulatory framework as well as a lack of market provided developer and end-user finance. Enabling factors were mainly the withdrawal of the government in the provision of housing in line with World-Bank neoliberal orthodoxy and incapacitation of the local authority, which eliminated alternative sources of housing for the low income group other than market provided housing, thus widening the market base for the developers. Strategies used by the developers include developer provided finance to the target group, preselling developments, sidestepping the local authority through buying land at the periphery of the local authority boundary, sidestepping regulatory barriers through engaging in corruption, backward integration to promote efficient resource allocation, and an innovative approach to risk management that caters for the low-income group. The study concludes that all these strategies have one overriding objective of cost containment. The findings indicate that there is potential, appetite and scope for more private-sector engagement. On this basis, it is recommended that the key to unlocking this potential lies with the state, as there are several policy implications that flow from these findings if the highlighted constraints are to be addressed. The study makes a number of key contributions to knowledge on market solutions to the low-income housing challenge in the area of theory, methodology, policy and empirical data.